Effective control of harmful Microcystis blooms by paucibactin A, a novel macrocyclic tambjamine, isolated from Paucibacter aquatile DH15. (10th January 2023) - Le, Ve Van; Ko, So-Ra; Kang, Mingyeong; Oh, Hee-Mock; Ahn, Chi-Yong
Abstract: Global warming and eutrophication accelerated Microcystis blooms, causing water quality deterioration. Cyanocides produced by cyanobactericidal bacteria have attracted substantial attention for controlling Microcystis blooms owing to their environmental friendliness. However, their application is still in the early stages, highlighting the need for the discovery of novel cyanocides. Herein, we isolated and purified a novel macrocyclic tambjamine produced by Paucibacter aquatile DH15, named paucibactin A. The cyanocidal activity of paucibactin A (1 μg/mL) against Microcystis (10 6 cells/mL) was 81.6% after 24 h of exposure. Paucibactin A killed Microcystis by destroying its structural integrity, photosynthetic and antioxidant systems, and macromolecules. The expression of the key genes involved in these fundamental processes in Microcystis was downregulated after paucibactin A treatment. In a microcosm study, paucibactin A (1 μg/mL) exhibited selective cyanobactericidal activity against Microcystis and Dolichospermum but not against other cyanobacteria. However, 87.4% of paucibactin A was degraded by photolysis in 24 h. Cyanobactericidal processes promoted the growth of eukaryotic microalgae, possibly by altering the competitive relationship and inducing changes in the bacterial community and interaction network. Collectively, our findings suggest that paucibactin A could be an effective cyanobactericidal compound for controlling Microcystis and Dolichospermum blooms. Graphical abstract: Image 1 Highlights: The first report of a macrocyclic tambjamine with cyanobactericidal activity. Paucibactin A is a novel cyanocide for controlling both Microcystis and Dolichospermum blooms. Paucibactin A destroys photosystems and induces oxidative stress in Microcystis. Paucibactin A is degraded quickly after bloom removal, leaving no secondary pollution.